Ömer B. İsa Ed-Dehlakî ve Lübâbü’l-Elbâb fî Fezâili’l-Ashâb adlı eseri (tahkik-tahlil-tercüme) - Shakori, Abdul Shakor (My University, 2022)
Klasik yazma eserlerin tespit edilmesi, tahkik edilerek ilmî çalışmalar ışığında gün yüzüne çıkarılması ve ilim dünyası ile araştırmacıların istifadesine sunulması büyük önem taşımaktadır. Yazması tespit edilen ve Doktora tez konusu olarak çalışılan Lübâbü’l-elbâb fî fezâili’l-ashâb adlı yazma, varlığı bilinen ancak yayınlanmamış olan bu nitelikte eserlerden biridir. Eser, hicrî V. asrın sonları ile VI. asrın ilk yarısında yaşamış olan Ömer b. Îsâ ed-Dehlakî tarafından kaleme alınmıştır. Lübâbü’l-elbâb’ın tahkik, tahrîc ve tercümesi büyük önem taşımaktadır. Zira eser; hadis, genel olarak sahâbe ve Hulefâ-i râşidîn’in faziletini ortaya koyma anlamında Farsça olarak kaleme alınan ilk kitaplardan biridir. Müellif eserinde, Rasûlüllah’ın ashâbının faziletini ortaya koyma anlayışıyla hareket etmiş, bunu da âyet, hadis ve tarihî rivâyet aktarmak suretiyle yapmıştır. Hadis âlimlerinin ve Ehl-i sünnet’in çizgisini takip eden Dehlakî, bu çizgiden ayrılan fırkaların ve müntesiplerinin sahâbe ve Hulefâ-i râşidîn hakkında ürettikleri bir takım şüpheler, düştükleri bazı hatalar ve yaptıkları çeşitli iftiralara aklî ve naklî deliller getirerek cevap vermektedir. Bir mukaddime ve beş bab üzerine telif edilmiş olan eserin mukaddime kısmında Ehl-i sünnet itikadı özetlenmiş, ilk dört babta hilâfete geçiş sırasına göre Hulefâ-i râşidîn üzerinde durulmuş, kendileri ile ilgili rivâyetler ve bilgiler sıralanmış, beşinci babta ise genel olarak sahâbenin fazileti ve önemine vurgu yapılmıştır. İki yazma nüshası tespit edilen ve ikisi de Türkiye kütüphanelerinde bulunan eserin, Farsça konuşan ve sahâbe konusunda hatalı anlayışları bulunan Şîa mezhebi müntesiplerine doğru sahâbe anlayışını öğretmek maksadıyla kaleme alındığı anlaşılmaktadır.

There is no doubt that the identification and investigation of classical manuscripts and bringing them into prominence and making these manuscripts available to the scientific world and researchers in the light of scientific studies is a crucial work. The manuscript named Lubabu’l-albab fi fadaili’l-ashab, which is determined and studied as a doctoral thesis, is one of the works of this nature, which its existence is known but has not yet been published. The manuscript was written by Umar b. Isa ed-Dehlaki who was living in the end of the V. and the first half of VI. Century Hijra. The verification, and translation of this work is momentous. Since the work is one of the first books written in Persian in the field of Hadith and specially in the sense of revealing the virtue of the Companions and the Hulefa-i rashidin in general. In his work, the author focuses on the understanding of revealing the virtue of the Companions of the Messenger of Allah, and he does this by quoting verses, hadiths and historical narrations. Following the line of hadith scholars and Ahli sunnah, Dehlaki responds to some doubts, mistakes and various slanders made by the sects and their followers, who departed from the line of Ahl as-sunnah, about the Companions and the Hulefa-i rashidin by providing rational and narrative evidence. In the introduction part of the authors work, The belief of Ahli sunna was summarized which was written on one introduction and five chapters. In the first four chapters, the Hulefâ-i râşidîn was emphasized according to the order of transition to the caliphate, the narrations and information about them were listed. In the fifth chapter, the virtue of the Companions in general and its importance is emphasized. It is understood that the work, of which two manuscript copies have been identified and both of which are in Turkish libraries, was written in order to teach the correct understanding of the companions to the followers of the Shia sect, who speak Persian and have erroneous understandings of the companions.
Keywords: Dehlakî; Hadis; Hadîs; Hadith; Hulefâ-i râşidîn Dahlaki; Islam; İslam; Khulafa-i rashidin; Lubab al-albab; Lübâbü’l-elbâb